A Thematic Roles Analysis Of Simple Sentences Found On The Titles Of China Daily Newspaper - Liyaningsih, Sri, Dra. Siti Zuhriah Ariatmi, M.Hum (2016)
The research aims at (1) describing the role played by each NP in an event and (2) describing the sentential context of the titles. The type of this research is descriptive qualitative research. The data source is the China Daily newspaper which is published in June-August 2015. Method of collecting data is documentation with the techniques as follows: (1) reading the China Daily newspaper that is published in June-August 2015, (2) selecting for the titles which is containing simple sentences, (3) collecting the selecting data, and (4) coding the data. In analyzing the data the writer uses the theory thematic roles of Kearns (2002) and Frawley (1992), and in explaining the sentential context the writer found it in the body of the text of the newspaper. The result of the study shows that there are twelve role played by the NPs in the events found in the titles of the China Daily Newspaper which is published in June-August 2015 they are Agent, Patient, Theme, Goal, Location, Beneficiary, Instrument, Experiencer, Stimulus, Purpose, Reason, and Time that is divided in thirty four patterns. They are classified into five which is starting by agent (77 data/60,64%), theme (23 data/18,11%), experiencer (12 data/9,46), patient (13 data/ 10,22%), and beneficiary (2 data/1,57%). The most dominant role in this research is agent role, in the form of active sentences, NP1 functioning as agent. The sentetial context of the titles can be found on the body of the text of the newspaper by paraphrasing it in order to make it to be clearer and comprehensive. Keywords : simple sentences, thematic roles, sentential context, China Daily newspaper.